2015
DOI: 10.1155/2015/469879
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty for Rapidly Destructive Coxarthrosis in a Patient with Severe Platelet Deficiency due to Liver Cirrhosis and Immune Thrombocytopenic Purpura

Abstract: Rapidly destructive coxarthrosis (RDC) causes rapid and extreme destruction of the hip joint, which was reported by Postel and Kerboull. RDC is commonly unilateral and occurs mostly in elderly women. Immune thrombocytopenic purpura (ITP) is characterized by a low platelet count that is the result of both immune-mediated platelet destruction and suppression of platelet production. In patients with ITP undergoing surgery, bleeding associated with a low preoperative platelet count can lead to unsuccessful outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Several potential risk factors have been proposed in the literature, including: (I) ageing; (II) female gender; (III) underlying health problems such as rheumatoid arthritis, diabetes mellitus and systemic lupus erythematosus; (IV) lower bone mineral density; (V) higher BMI; (VI) medicinal drug use including NSAIDs and corticosteroid; (VII) alcoholism (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)27,29). In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the o...…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several potential risk factors have been proposed in the literature, including: (I) ageing; (II) female gender; (III) underlying health problems such as rheumatoid arthritis, diabetes mellitus and systemic lupus erythematosus; (IV) lower bone mineral density; (V) higher BMI; (VI) medicinal drug use including NSAIDs and corticosteroid; (VII) alcoholism (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24)27,29). In this study, we evaluated the risk factors and found the only prevalent factors were: (I) age greater than 60 years; (II) female gender; (III) underlying systemic disease such as rheumatoid arthritis, diabetes mellitus or systemic lupus erythematosus (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)23,24). There is insufficient evidence to support the relationship between BMD, BMI, medication and alcoholism and the o...…”
Section: Discussionmentioning
confidence: 99%
“…Yuasa et al reported that after an average follow-up duration of 9.3 years, the mean Harris Hip Score improved from 38.3 to 81.1 in RDA patients and from 43.6 to 84.2 in conventional osteoarthritis controls (15). During surgery, the total blood loss of patients with hip osteoarthritis was significantly less than patients with RDA (9,14,16,35). Sex, age and extra body weight (BMI) had no significant effect on bleeding (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations